Analisis Kinerja Operasional Angkutan Peti kemas PT. Kereta Api Logistik Terhadap Kepuasan Pelanggan (Studi Kasus Rute Stasiun JICT-Cikarang Dry Port) - Azhari, Nabil; Lesmana, Rizky Williyanto (Institut Transportasi dan Logistik Trisakti, 2024)
PT. Kereta Api Logistik JICT Station West Area 1 is a subsidiary formed by PT. Kereta Api Indonesia (Persero) based on Deed No.10 dated September 8, 2009. PT. Kereta Api Logistik was formed to serve rail-based logistics distrtribution with door to door service. This research method uses quantitative methods and then processed using Customer Satisfaction Indeks (CSI) analysis to mesuare customer satisfaction, and Importance Performance Analisysys (IPA) method to mesuare perceptions at the performance level and cunsumer expectations at the level of customer importance. Based on the results of the analysis obtained, the result of the level of conformity score is 97.38%. This result shows almost perfect. And the results of the reliability of 0.8 can be stated that all statements are reliable with a very good level of reliability. However, the company still needs to improve several indicators consisting of the amount done (-0.2), the quality of work produced (-0.1), attendance (-0.1), ability to work together (-0.1), service quality (-0.2), price (-0.2), and situational factors (-0.2). For punctuality and personal factors have been well realized.